Male Breast Cancer Originating in an Accessory Mammary Gland in the Axilla: A Case Report - Jun Yamamura; Norikazu Masuda; Yoshinori Kodama; Hiroyuki Yasojima; Makiko Mizutani; Keiko Kuriyama; Masayuki Mano; Shoji Nakamori; Mitsugu Sekimoto (Case Reports in Medicine)
Carcinoma of an accessory mammary gland is an extremely rare tumor. A 61-year-old male patient presented with a hard mass measuring 85 mm × 51 mm in the left axilla. Incisional biopsy histopathologically showed an adenocarcinoma compatible with breast carcinoma originating in an accessory mammary gland. Systemic examinations revealed no evidence of malignant or occult primary lesion in the bilateral mammary glands or in other organs. Neoadjuvant chemotherapy was performed for the locally advanced axillary tumor and reduced the tumor to 55 mm in size, and, then, he could undergo complete resection with a negative surgical margin in combination with reconstructive surgery to fill the resulting skin defect with a local flap of the latissimus dorsi muscle. The patient has presented with no metastatic lesion in four years since the operation. This unusual case shows that neoadjuvant chemotherapy is an effective and tolerated therapy for advanced accessory breast cancer in the axilla.